Leading students towards a new soft-skills perspective: development for employment - SHEHU LOKAJ, ALMA; Miftari, Vehbi; Hajdari, Vjosa (Journal of Education Culture and Society, 2021)
Aim. Based on similar studies, this research work aims to investigate the perception of students and Higher Education Institutions (HEIs) of learning about the importance of soft skills for their education and employment since these skills are increasingly sought-after by potential employers. Methods. The Kendall Tau b test and Mann Whitney U test have been applied to show the relationship between soft skills and job preparedness for students. This study investigates a selection of 100 students from a private HEI (UBT College) and 100 students from a public HEI (University “Haxhi Zeka”), both in Kosovo. A total of 200 valid responses were collected from July to September 2020. Goldsmith inventory for 15 soft skills has been distributed as a questionnaire has been distributed to the students of these universities. Results and conclusion. The research results indicate that in soft skills development of the UBT College students is significantly higher than the soft skills developed of the University “Haxhi Zeka” students. The findings also show that most of the students believe that their actual soft skills were at a less than the desired level. Practical application. This research implicates the Higher Education Institutions to consider the soft skills as an important tool for enhancing graduates’ employability. The results indicate the need to reconsider the curriculum by embedding soft skills on it. The students’ perception on soft skills is a contribution not only for the universities considered in this research but also for all graduates in HEIs in Kosovo, since the curriculum does not change much among universities. According to Eurostat the unemployment youth rate in Kosovo is about 55.4% and for this reason the results will help the HEIs to rethink about their students’ future employment opportunities. Originality. This is the only study done in Kosovo about graduates’ soft skills and employment and it provides information about a concerning problem in the country. This paper suggests initiatives to upgrade students’ soft skills and to improve their perspective on their future employment.